Identifying the key steps determining the selectivity of toluene methylation with methanol over HZSM-5 - Qingteng Chen (Nature Portfolio, 2021)
The selectivity of zeolite catalyzed toluene methylation is still under debate. Here the authors report a comprehensive theoretical investigation based on ab-initio molecular dynamics to identify the key-steps of methylation of toluene with methanol over a zeolite to produce p-xylene.